Blood pressure variability in the elderly. Association between postprandial and sleeping periods - Garcia,Fernando Abrão (2017)
Abstract Introduction: The variability of arterial blood pressure (BP) is considered an important cardiovascular risk factor. Objective: To verify the possible associations between the postprandial and the sleeping blood pressure variability. Methods: This study evaluated systolic, diastolic, mean, pulse pressures and heart variability in 69 elderly patients in preprandial, postprandial and sleeping periods. One 24 hours ambulatory blood pressure monitoring was used for measurements and the results were showed in the time-rate index. Results: We observed a decrease in the systolic blood pressure values from preprandial to postprandial and to the sleeping periods (124.7 ± 14.6, 113.2 ± 15.3 and 108.5 ± 13.9mmHg, respectively; p = 0.003). Associations between BP variability of the postprandial and sleeping periods were obtained for systolic, diastolic and mean arterial pressure. Conclusion: The correlation between postprandial and sleeping BP variability has rarely been demonstrated in the literature. These correlations between BP changes after eating and during sleep might suggest that both events could coexist in other clinical situations.